PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH - Toyyibul Imam (Jurnal Manajerial, 2017)
The research is aimed : 1) to determine the relationship marketing variables that consists of trust, commitment, communication, bonding and satisfaction partial effect on customer loyalty. 2) to determine the relationship marketing variables that consists of trust, commitment, communication, relationship and simultaneously influencing satisfaction on customer loyalty. In this study has six hypotheses to be tested using multiple linear regression. Sampel used in this study were drawn from the Bank BCA Syariah customers consisting of 80 respondents. This research using quantitative methods and sampling techniques incidental. The results of the data processing SPSS version 15. The result of t-test research shows that t < t tabel is -0,441 < 1,993 then the trust is not a positive effect on customer loyality, t count > t tabel is 3,821 > 1,993, this shows that the commitmen has a positive effect on customer loyality, t count > t tabel is 3,468 > 1,993, this show that the communicationt has a positive effect on customer loyality. t count > t table is 2.669> 1.993, then the bond has a positive effect on customer loyalty , t count> t table is 2.691> 1.993, the satisfaction has a positive effect on customer loyalty . The results of the study showed that the test F 25.155 F count> F table 2.33 and the significance of the F values were less than 0.05 (0.000 <0.05) the trust, commitment, communication, bonding and satisfaction simultaneously influence on customer loyalty.